(3MhGOK GdbQGfGJs - (3CHh GdYHGS GdaVd Hf MGJe GdfjQjRis ((3MGLi Ydi GdQGRi s)
(3ChdgG (B:s
(3bGd CHh GdYHGS Ef GdPi MOGfi Ydi ESJNQGL eG OhfJg ai gPg GdebGdI hPcQJg ef ebGQfGJ GdchGcH GdYdhjI hGdcdGe Ydi XghQ GdaJf HGdZQH , heG EJUd HPdc ef GdcdGe Ydi GdOhd s
(3BNQgG (B:s
(3hEf cGf HQLkG efbdHkG fXQJ WhGdY ONhd GdTeS ChGFd SGFQ GdHQhL HMhd Gddg JeJ ebGdI GdaVd Hf MGJe GdfjQjRi ai GdbQGfGJ hGdcShaGJ hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B297 - (3U(B307s
(3HgG fXGe GdJYbjHIs
(3cJHJ fbdkG Yf fSNI LeYgG EHQGgje GdMGSH GdeGdci GdefUhQi GdfGUQi HeOjfI GdbGgQI SfI (B759 (3g`s
(3HChd GdeLehYI Jedc dSfI (B1249(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs